Seclusion as a necessary vs. an appropriate intervention: a vignette study among mental health nurses. Issue 4 (May 2015) - Mann‐Poll, P. S.; Smit, A.; Koekkoek, B.; Hutschemaekers, G.
Abstract : Accessible summary: The use of seclusion is either based on the necessity of its use or on the appropriateness. Factors of influence on both decisions are unclear. In a vignette study, mental health nurses were asked to score vignettes on a necessity and an appropriateness Likert scale. Although seclusion was scored significantly higher on necessity, factors of influence and underpinning patterns were shown largely the same. According to the theory of Festinger, focusing on a greater discrepancy between necessity and appropriateness is seen as a necessary condition to achieve a reduction in the use of seclusion. Abstract: In a vignette study, mental health nurses were asked to score vignettes on necessity and appropriateness using a Likert scale. Sixty‐nine clinical nurses from four mental health institutes scored 64 vignettes on necessity (there is no alternative) and appropriateness (seclusion supports patients' treatment) of seclusion simultaneously. Data analysis focused on the differences between both scores, and included general linear model analysis, t ‐test statistics and Kendall's tau. The t ‐test resulted in a significantly higher score on necessity than on appropriateness. Differences between both scores could be explained for 32% by a combination of nurse characteristics and vignette variables. Necessity and appropriateness were found to be strongly associated with each other, showing that underpinning patterns were largely the same. This research enhances the understanding of underlying factors that influence the decision of nurses to use seclusion. This is essential for the development of interventions aimed at the reduction of seclusion use in mental health practice.